Plexo braquial de mamíferos e aves: revisão de literatura - Ricci, Dela Gisele [UNESP]; Guazzelli Filho, Joffre [UNESP]; Silva, José Ricardo de Carvalho Pinto e [UNESP]; Matheus, Selma Marcia Michelin [UNESP]; Filadelpho, André Luiz (My University, 2013)
The brachial plexus is formed by the ventral rami of spinal nerves that innervate the forelimb and shoulder girdle. In dogs and cats branches are C6, C7, C8, T1 and T2. In monotrema the origin of the brachial plexus is in T1 up to C4, as well as in lemurs. In young men from C6 to T2, the chinchilla C7 to T1 and mice from C5 to T1. In turkey C12, C13 and T1com participation of T2. In vulture with origins from 4 rami of C11 to T2.

O plexo braquial é formado pelos ramos ventrais dos nervos espinais que inervam o membro torácico e a cintura escapular. No cão e no gato os ramos são C6, C7, C8, T1 e T2. No monotrema a origem do plexo braquial esta em C4 ate T1, assim como nos lêmures. Nos mócos de C6 a T2, na chinchila de C7 a T1 e nos ratos de C5 a T1. No peru de C12, C13 e T1com participação de T2. No urubu com origens a partir de 4 ramos, de C11 a T2.
Brachial plexus of mammals and birds: review
Keywords: Anatomy; Nerves; Spinal cord; Birds; Mammals; Anatomia; Nervos; Medula espinhal; Aves; Mamíferos